MicroRNA‐125a inhibits tumorigenesis by targeting Smurf1 in colorectal carcinoma - Dongbin Li; Xiangmei Xu; Jihao Miao; Jianhui Cai (FEBS Open Bio)
Aberrant expression of microRNAs (miRNAs) may contribute to the initiation and development of multiple types of human cancer. Several miRNAs have been found to be strongly correlated with the diagnosis, progression, and prognosis of colorectal carcinoma (CRC), but the role of miR‐125a in CRC remains unclear. In the present study, the function of miR‐125a on the expression of Smad ubiquitin regulatory factor 1 (Smurf1) was investigated in vitro and in vivo. We verified that Smurf1 is a downstream target gene of miR‐125a and is involved in miR‐125a‐mediated regulation of CT26 cell (colon cancer cell) proliferation and migration. Overexpression of miR‐125a suppresses CT26 cell growth by inhibiting cell proliferation. Additionally, wound healing assays were performed to show that overexpression of miR‐125a significantly reduced CT26 cell migration, which was reversed by overexpression of Smurf1. In vivo, miR‐125a overexpression downregulated the expression of Ki67 and Smurf1, thus leading to a marked reduction in tumor growth. These results revealed that miR‐125a plays a critical role in CRC by directly targeting Smurf1, a finding that may facilitate the development of improved diagnostic and therapeutic techniques for CRC.